Adsorption and mechanistic study for phosphate removal by magnetic Fe3O4-doped spent FCC catalysts adsorbent. (March 2019) - Yuan, Ling; Qiu, Zhaofu; Yuan, Lin; Tariq, Muhammad; Lu, Yunqing; Yang, Ji; Li, Zhen; Lyu, Shuguang
Abstract: The waste materials utilization has attained increasing attention due to the generation of a large number of spent materials. In the current study, a practical magnetic adsorbent (Fe3 O4 -doped spent Fluid Catalytic Cracking catalysts, abbreviated as FCCx @(Fe)y -O) was prepared, liable to be separated. The batch experiments were employed to investigate the phosphate removal behavior. The findings of this study demonstrated that FCC4 @(Fe)1 -O exhibited the best phosphate removal performance among the adsorbents (FCCx @(Fe)y -O), attributed to rough surface layer, i.e., composed of active sites. The various characterizations results revealed that the adsorption behavior of FCC4 @(Fe)1 -O followed the inner-sphere adsorption based on ligand exchanges mechanism. Furthermore, OH − played an important role in the adsorption process. Minor effects were showed on the phosphate removal in the experiments of commonly coexisting anions, except CO3 2− and SiO3 2− . The above findings affirmed that FCC4 @(Fe)1 -O was a suitable adsorbent for phosphate removal in the practical application. Graphical abstract: Image 1 Highlights: Magnetic adsorbents were prepared with spent FCC catalysts based on waste utilization. FCC4 @(Fe)1 -O could efficiently remove phosphate with extensive range of pH. FCC4 @(Fe)1 -O quickly separated from the aqueous solution, shorter than 2 min. The underlying mechanism was inner-sphere complexation based on ligand exchange.